The 1976 Illini: Sweet Memories of Alma Mater - Dutt, Diya (Education Policy Analysis Archives, 1996)
The purpose of this article is to explore the attitudes of graduates of the class of 1976 from the University of Illinois toward their alma mater over a period of fifteen years. The central question addressed in this article is: How do former students feel about their educational institution as time passes? Early research suggests that students' attachment to their educational institution becomes weaker with the passage of time. This panel data on alumni attitudes towards the academic environment indicates that contrary to evidence from past research, students developed a stronger attachment towards the educational institution with passage of time. A similar positive pattern was evident when examining the attitude towards the program major. It is possible that better experiences in the real world have made the alumni comprehend the quality of education they received at the University of Illinois. Also, favorable disposition toward one's institution seems to be, to a very considerable extent, the college's contribution to the intellectual development of the student.